Implementasi Aplikasi Auto Index untuk Manajemen Arsip SPT dan SPPD DPRD Kota Bengkulu - Witriyono, Harry; Adirizki, Bintang Andika; Nabhan, Darry; Habibila, Kevin Eza; Riski, Nofran; Hidayat, Adika Fajri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This activity discussed the implementation of the Auto Index application in the management of Duty Warrant (SPT) and Official Travel Warrant (SPPD) archives at the Bengkulu City DPRD. This system was developed as a digital solution in improving the efficiency of the filing process and making it easier to search for documents faster and more accurately. This street vendor activity has been carried out at the Bengkulu City DPRD Building from February 3 to February 28, 2025. The implementation stages carried out are needs analysis, system design, and implementation and testing. The results of a survey of employees who use this system show that 85% of users find this application very helpful in their work, especially in finding documents quickly. Thus, the implementation of the Auto Index in the Bengkulu City DPRD has had a positive impact on the efficiency and effectiveness of archive management.